Development of Regional Production and Logistic Networks in East Asia: the Case of the Philippines - Fatima del Prado; Mari-Len R. Macasaquit; Michael R. Cabalfin; Melalyn C. Mantaring (Philippine Institute for Development Studies (PIDS), 2010)
Regional production networks and local production linkages are important not only for the generation of industrial activity through investment flows but also as essential sources of new information and technology. Complementing this are the so-called knowledge networks within or around industrial agglomerations that are equally important sources of technology for industrial upgrading and innovation. Both are present in the case study area of CALABARZON in the Philippines but the former seem to be more apparent than the latter as this has been characterized as weak based on secondary data and conduct of survey of establishments. With weaknesses in the S&T system in the country as part of the study's findings, policy suggestions were provided to strengthen the linkages that remain to be wanting but are important for stimulating innovation.
Keywords: 330; manufacturing sector; innovation; Philippines; global production networks (GPNs); industrial agglomeration; industrial development; production linkage; Regionale Wirtschaftsintegration; Regionales Cluster; Standortpolitik; Philippinen